2014
DOI: 10.1038/ajg.2013.419
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Long-Term Follow-Up After Endoscopic Resection of Large, Nonpedunculated Colorectal Lesions: A Prospective Two-Center Study

Abstract: A detailed study design with systematic biopsies of inconspicuous scars reveals a significant number of residual adenomas after completed resection. However, these residual neoplasias can be effectively treated at follow-up colonoscopies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
95
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 21 publications
4
95
4
3
Order By: Relevance
“…This underlines the fact that cases included in the studies are likely to remain difficult to treat despite the help of the combined techniques, but it could also suggest that the combination of the two techniques does not necessarily make things easier. In any case, the management of these complications requires secondary surgery in 3% of the cases, which is also slightly more than the incidence of further surgery after standard endoscopic polypectomy 25 and comparable to the results of laparoscopic standard resections. 10 In fact, laparoscopic right and left colectomy are burdened by about 8% overall complication rate, 26 which requires further surgery in about 2% of cases, 27 which is slightly lower than the results from the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This underlines the fact that cases included in the studies are likely to remain difficult to treat despite the help of the combined techniques, but it could also suggest that the combination of the two techniques does not necessarily make things easier. In any case, the management of these complications requires secondary surgery in 3% of the cases, which is also slightly more than the incidence of further surgery after standard endoscopic polypectomy 25 and comparable to the results of laparoscopic standard resections. 10 In fact, laparoscopic right and left colectomy are burdened by about 8% overall complication rate, 26 which requires further surgery in about 2% of cases, 27 which is slightly lower than the results from the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a counterpart of the high incidence of secondary surgery the recurrence rate is relatively low, being set at 5.4% which is lower that standard polypectomy, 25 although still consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, we have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 8 observed that gastroenterology fellows uniformly think that clip artifact is residual polyp the first time they are exposed to it. We 2 and others 3 have reported that biopsy specimens of endoscopically normal-appearing EMR sites will sometimes reveal residual dysplastic or serrated tissue. We previously showed that residual tissue on histology but not evident by endoscopy is associated with a higher risk of an eventual or "late" recurrence of polyp in the EMR site 2 .…”
Section: Discussionmentioning
confidence: 99%
“…emphasized that there is value in taking biopsy specimens from the EMR site even at the second follow-up when the site appears endoscopically normal 3 . We make an exception to the timing of follow-ups if the first follow-up shows a visible recurrence that is either large or has high-grade dysplasia (both are rare).…”
mentioning
confidence: 99%
“…Notably, biopsy evidence of residual or recurrent adenomas was found in 7% of polypectomy scars that were macroscopically normal. 8 Another recent large series from Australia included 1000 successful colorectal EMRs: 80% had an early follow-up with a 16% rate of residual/recurrent adenomas, even if mostly minimal; and of the 670 cases with a normal first control colonoscopy, only 426 had a second follow-up within the study, revealing a 4% recurrence rate. 9 The price for the high overall effectiveness of colorectal EMR (98% in the Australian study) is, therefore, the consequent performance of several follow-up colonoscopies within the first 2-3 years.…”
mentioning
confidence: 99%